Optimising geometry and asymmetrical damping ratio to reduce vehicle vertical acceleration under stochastic road profile - Fernandes, J. C. M. [UNESP]; Silveira, M. [UNESP]; Desmet, W.; Pluymers, B.; Moens, D.; Rottiers, W. (Katholieke Univ Leuven, Dept Werktuigkunde, 2018)
This work presents a study on the dynamic behaviour of a vehicle suspension system with asymmetrical viscous damping, with stochastic road profile. The geometrical configuration of a double-wishbone suspension system is taken into account, so as to include geometrical nonlinearities. It is known that the use of asymmetrical damping can diminish the sprung mass acceleration, and causes a shift of the mean position of the sprung mass. The optimum configuration of the geometrical parameters and the asymmetry ratio that minimises the vertical acceleration of the vehicle body is seeked. The lengths of the lower and upper arms and the inclination of the spring-damper assembly are the geometrical parameters considered in the optimisation. Numerical simulations showed that the optimised system presents a reduction close to 30 % in the RMS acceleration. The optimised parameters depend on the chosen asymmetry ratio of the damper, in agreement with previous result showing the influence of asymmetry ratio on the acceleration of the sprung mass.